Chemical profiling of Curcuma aeruginosa Roxb. essential oil and their antimicrobial activity against pathogenic microbes - Abdul Aziz, Julia; Saidi, Noor Baity; Ridzuan, Raihana; Mohammed, Abdul Karim Sabo; Abdul Aziz, Maheran; Abdul Kadir, Mihdzar; Abdullah, Nur Ashikin Psyquay; Hussein, Sobri; Yusoff, Hamidah (Taylor and Francis, 2021)
Curcuma aeruginosa from the Zingiberaceae family has been cultivated for its traditional and medicinal properties in Malaysia. This study aimed to investigate the volatile constituents of C. aeruginosa essential oil from Malaysia and evaluate its antimicrobial properties compared to C. aeruginosa essential oil from other countries. The essential oils were obtained from fresh and dried leaves and rhizome of C. aeruginosa using the hydrodistillation method and analyzed using gas chromatography-mass spectrometry (GC/MS). The highest essential oil yield was obtained from dried rhizome at 0.63 % (w/w). The major volatile constituent found in the essential oil isolated from fresh leaves were 1,8-cineole (7.91 %), curzerene (5.16 %), and germacrone (4.91 %); dried leaves contained 1,8-cineole (17.21 %), camphor (6.55 %) and curzene (3.85 %); fresh rhizomes contained 1,8-cineole (20.53 %) and camphor (6.08 %) whereas dried rhizomes contained 1,8- cineole (18.41 %), camphor (9.89 %), and DL-isoborneol (3.13 %). The essential oils showed good antibacterial and antifungal activity against Staphylococcus aureus, Bacillus subtilis Escherichia coli, Aspergillus niger Candida albicans but were not effective against Serratia marcescens. This study highlights the variation in the volatile constituents of C. aeruginosa essential oil from different countries and the antimicrobial potential of C. aeruginosa essential oil from Malaysia, which may be used against various bacterial and fungal species.